2022
DOI: 10.1177/19476035221074000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes and Pathways Associated with Oxidative Stress of Cartilage in Osteonecrosis of Femoral Head Using Bioinformatics Analysis

Abstract: Objective This study aimed to identify the hub genes and pathways of genes related to oxidative stress of cartilage in osteonecrosis of femoral head (ONFH), and to predict the transcription factors of the hub genes. Methods The GSE74089 was obtained from the Gene Expression Omnibus (GEO) database, including 4 necrotic tissues and 4 normal tissues, and the differentially expressed genes (DEGs) were identified by limma package in R language. Simultaneously, we searched for the genes related to oxidative stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…14 In addition, TFAP2A is discovered to be a transcription factor of the hub genes. 26 Zhang et al 27 found that RELA and TFAP2A are transcription factors connected to cerebral ischemia-reperfusion injury, which are mostly involved in pathways having to do with inflammation. Furthermore, Jiang et al 28 demonstrated that TFAP2A and RELA selectively modulate gene expression in glioma by physically binding to the promoter region of these genes that are mainly relevant to the regulation of the immune system and cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In addition, TFAP2A is discovered to be a transcription factor of the hub genes. 26 Zhang et al 27 found that RELA and TFAP2A are transcription factors connected to cerebral ischemia-reperfusion injury, which are mostly involved in pathways having to do with inflammation. Furthermore, Jiang et al 28 demonstrated that TFAP2A and RELA selectively modulate gene expression in glioma by physically binding to the promoter region of these genes that are mainly relevant to the regulation of the immune system and cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Shi et al suggests that RELA is the hub gene of genes related to oxidative stress in cartilage for those suffering from osteonecrosis of the femoral head. In addition, TFAP2A is discovered to be a transcription factor of the hub genes 26 . Zhang et al 27 found that RELA and TFAP2A are transcription factors connected to cerebral ischemia–reperfusion injury, which are mostly involved in pathways having to do with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, results of mRNA microarray analysis and RT-qPCR indicated that 6 genes were increased in DEX-treated MLO-Y4 cells, and SP1 mRNA was decreased with APS treatment. Shi et al reported that SP1 was a vital regulatory factor of hub genes in osteonecrosis of femoral head [ 32 ]. We demonstrated that SP1 reversed the effects of APS on osteocyte autophagy and apoptosis in DEX-treated MLO-Y4 cells, suggesting that APS promotes autophagy and inhibits apoptosis in SONFH cell model via reducing SP1 level.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 signaling pathway can play a more auxiliary role in activating RA broblast-like synovial cell (FLS), which has a strong regulatory effect on osteoclast formation and provides a basis for targeting IL-17-related pathways in the therapeutic regulation of arthritis in ammation [39,52]. The MAPK signaling pathway modulates a variety of biological processes and cellular functions [53].Surprisingly, Schisandrin A has been reported to inhibit the expression of IL-1β through MAPK signaling and NF-κB signal pathways [54], improve the in ammatory microenvironment and reduce cartilage absorption [54,55].In addition, the MAPK-activated protein kinase 2 (MK2) inhibitor decreased the production of HGF,IL-12B,CXCR3, etc., It plays a role in the treatment of immune-mediated in ammatory arthritis such as RA [56]. Consequently, the MAPK signal pathway is crucial for the maintenance and treatment of RA-induced ONFH.…”
Section: Discussionmentioning
confidence: 99%